Curing of plasmid pBMB28 from Bacillus thuringiensis YBT‐020 using an unstable replication region. (10th September 2015) - Wang, Pengxia; Zhu, Qian; Shang, Hui; Zhu, Yiguang; Sun, Ming
Abstract : Bacillus thuringiensis serovar finitimus strain YBT‐020 is the well‐studied spore‐crystal association (SCA) phenotypic strain, whose parasporal crystals adhere to spore after lysis of the mother cell. Its endogenous plasmids pBMB26 and pBMB28 were proved essential for this SCA phenotype. In our previous study, using conventional methods, pBMB26 cured derivative and both pBMB26 and pBMB28 cured derivative of YBT‐020 were obtained. However, YBT‐020 solely cured of pBMB28 could not be obtained. In this study, an unstable replication region of pBMB28 was identified and was used to construct an incompatible plasmid pRep28B. This incompatible plasmid was successfully used to cure plasmid pBMB28 and was easily eliminated through segregational instability under the optimum growth temperature of YBT‐020. Therefore, an endogenous plasmid was cured from the B. thuringiensis strain utilizing plasmid incompatibility. Moreover, using an unstable replication region instead of a temperature sensitive (Ts) replication region is better to cure the incompatible plasmid because it can avoid culturing at higher temperature. This method provides an efficient method for plasmid curing in B. thuringiensis and other bacteria.